Crossing the Threshold from Founder Management to Professional Management: A Governance Perspective - Gedajlovic, Eric; Lubatkin, Michael H.; Schulze, William S. (Journal of Management Studies, 2004)
ABSTRACT We argue that the challenges faced by threshold firms are deeply rooted in governance characteristics (i.e. the incentives, authority and legitimacy) which imbue them with characteristic capabilities, disabilities and path dependencies. Whereas Zahra and Filatotchev (2004) reason the principal problem facing threshold firms relates to organizational learning and knowledge management, we posit resource acquisition and utilization to be equally important. Moreover, we argue governance theory is more able than a knowledge‐based perspective to explain the root causes of the learning and resource issues faced by threshold firms as well as the complex set of processes involved in their effective management.